Seribu islands in the megacities of Jakarta on the frontlines of the climate crisis - Setiawati, Martiwi Diah; Chatterjee, Uday; Djamil, Yudha Setiawan; Alifatri, La Ode; Nandika, Muhammad Rizki; Rachman, Herlambang Aulia; Supriyadi, Indarto Happy; Hanifa, Nuraini Rahma; Muslim, Aidy M.; Eguchi, Tsuyoshi; Prayudha, Bayu; Oktaviani, Aulia; et al. (Frontiers in Environmental Science, 2023)
This study aims to explore the evidence of local climate trends, the potential impact, and its policy intervention on Seribu Islands which are classified as small island states and widely recognized as being especially at risk from climate change, threatening their economic and social growth. Long-term in-situ climate data, satellite data, interview with local stakeholder and literature review were utilized in order to conduct an exploratory descriptive analysis. The result revealed that Seribu Island experienced a 2.2°C increase in minimum temperature from 1980 until 2021, 3.5-fold of the frequency of extreme temperature and precipitation, 4.17 mm/year of sea level rise, and 10.8 ha land expansion in the densest island. Moreover, about 67% of the inhabitant's islands were occupied by built-up areas that covers more than 50% of the region. Further under the worst-case SLR scenario, about 58.4% area will be affected and about 29 islands will be disappeared. This evidence was also reinforced by every single local respondent's viewpoint who felt that climate change is occurring in the region. Even though the region faces a severe threat of climate change, the issue of climate change adaptation has not been mainstreamed yet into their local policy. Therefore, the urgency of a real-time climate ground station, a real-time early warning system, and establishing a Regional Disaster Management Agency (BPBD) at the district level have yet to be addressed. Furthermore, the knowledge gained from such case studies is outlined, along with some scientific evidence that may assist small island states in better fostering the opportunities provided by climate change adaptation.